(untitled) (Swiss Medical Weekly, 2013)
BACKGROUND: Preventive implantation of an implantable cardioverter defibrillator (ICD) early after myocardial infarction failed to demonstrate a survival benefit in patients with depressed left ventricular ejection fraction (LVEF). This may be explained by early recovery of the LVEF after percutaneous coronary intervention (PCI). We sought to determine the incidence of a sustained LVEF ≤35% in patients with severely depressed LVEF early after a revascularised acute ST-segment elevation myocardial infarction (STEMI). METHODS: LVEF was assessed in patients with an acute STEMI treated with PCI in two Swiss high-volume centres within 10 days (in-hospital LVEF) after the STEMI. Those with an in-hospital LVEF ≤35% were scheduled for follow-up LVEF measurement within 6–8 weeks. RESULTS: A total of 330 patients were included (79% male, mean age 63 ± 12 years). In-hospital LVEF measured 3 ± 3 days after STEMI was ≤35% in 32/330 patients (10%, 95% confidence interval (CI) 13%–67%). LVEF was available in 31/32 (97%) patients at follow-up 53 ± 19 days after STEMI and improved to >35% in 19 patients (61%, 95% CI 42%–78%). The incidence of a LVEF ≤35% at follow-up was 39% (12/31, 95% CI 22%–56%). CONLUSION: Our data demonstrate that the incidence of severely impaired LV function 53 ± 19 days after a STEMI treated with PCI is low. A severely depressed LVEF early after STEMI was present in 10% of all patients. Only 39% of these patients had a persistently impaired LVEF during follow-up. These findings support an expectant strategy before considering primary preventive ICD implantation after STEMI.